First record of a hybodont shark (Chondrichthyes: Hybodontiformes): from the Lower Cretaceous of Colombia (2016)
The Mesozoic chondrichthyan fossil record from northern South America is scarce and poorly known containing only a few reports of lamniform and ptychodont species from the Upper Cretaceous of Colombia and Venezuela. Here, we report the discovery of two associated (found together) dorsal fin spines of a hybodont shark from the Valanginian deposits of the Rosablanca Formation (Andes of Colombia). This hybodont along with the presence of ammonites and other mollusks, turtles, plesiosaurs and ichthyosaurs support a marine depositional environment for this geological unit. Although both spines described here are fragmentary and without diagnostic characters to allow identification to generic level, their finding represents the first record of this shark group from northernmost part of South America and northwestern margin of Gondwana. This new record expands the known distribution of this group of sharks during Lower Cretaceous.